Professional Hazards of Agricultural Industry Workers - I. S., Manasova (American Journal of Biodiversity, 2025)
This article analyzes the main types of activities related to occupational safety and health hazards at flour mills in Bukhara. It provides a characterization of professional hazards related to adverse working conditions at flour milling enterprises. It also examines correlations between workers' health and their work. Through a survey, the level of awareness among workers about the dangers in the workplace is determined.